Empirical molecular modelling of crystal growth modifiers - Jones, Franca; Rohl, Andrew (Taylor & Francis Ltd, 2005)
Molecular modelling has been successfully used to interpret the effect of two molecules on the crystal growth of barium sulfate. The replacement energy was found to correlate with the degree of inhibition as determined from conductivity experiments. It was also able to predict the preferred barium sulfate face for additive adsorption. For EDTP (ethylenediaminetetramethylenephosphonic acid), the energetically favoured adsorption configurations were those where the phosphonate groups occupied vacant sulfate lattice sites, whilst for EDTA (ethylenediaminetetraacetic acid) it was generally not possible for all the carboxylate groups to lie within the surface and so surface barium cation to additive oxygen interactions became important. Whether in the surface or above it, the number of Ba-O modifier interactions were important in making adsorption of the modifier energetically favourable.